The Influential Powers in the Levant and Their Relationship with the Ottoman empire during the 18th Century - lassag, ameur; dahmani, toufik (The Algerian Historical Journal, 2026)
This study addresses the topic of local tribalism in the Levant during the 18th century and its relationship with the Ottoman Empire, considering it a significant force that influenced the events in the region. It discusses the Ottoman policy towards these tribes and families, both those supportive and loyal to the Ottomans in the area and those that took a negative stance, broke the obedience, and resorted to rebellion.This modest study reveals that those pro-Ottoman families and tribal groups in the Levant made considerable efforts to monopolize governance in their regions and maintain this privilege for long periods. This did not disturb the Ottoman authorities; on the contrary, they relied on these local forces to consolidate their rule in the Levantine provinces and to curb any movements opposing the Ottoman regime.It was also recorded that the leaders and tribes that revolted, despite the disturbances they caused, did not pose a significant threat to the Ottomans, as none of them dared to separate from the Ottoman state or demand independence. This can be attributed to several reasons clarified throughout this study.